(untitled) (Journal of Health Sciences, 2023)
Introduction: Laboratory personnel (LP) represent a high-risk group of healthcare workers for whom the primary laboratory environment and specific work activities are a major source of potential exposure to health hazards. This study aimed to evaluate the developed matrix and assess risk based on self-assessment. Methods: This multicenter, qualitative, and cross-sectional study was conducted on LP employed in biomedical laboratories. The respondents were divided into groups according to their territorial affiliation. The data collection tool used was a six-area questionnaire distributed online through a network of professional associations. For the risk assessment, a matrix was developed with scores ranging from 0 to 650, dividing the risk level into four categories. Descriptive and inferential statistical methods were used for the statistical analysis. Results: The developed model combined the classification of risk and risk factors with a certainty of p < 0.001. The regression analysis showed that working conditions had the greatest influence on overall risk, followed by physical, biological, and chemical hazards. Of the 640 respondents, the medium risk category was the highest in European Union (EU) countries (81.2%). Comparing the values in the high-risk category between the Bosnians and Herzegovinians (BiH) group and the Republic of Serbia, Republic of Northern Macedonia, and Montenegro (SCM) group with the EU group, a doubling (16.6%: 36.7%) and tripling (16.6%: 52.1%) of the proportion was found, respectively (p < 0.001). Overall, 1.7% of the LPs from BiH fell into the high-risk category. Conclusions: The designed matrix provides a reliable basis for identifying risk predictors in the study population and can serve as a useful tool for conducting risk assessments in biomedical laboratories. The results of the risk assessment indicate significant differences between the studied groups and highlight the need for increased control of BiH workplaces through new regulatory requirements.